To be or not to be supervisors for medical students in general practice clinical placements: a questionnaire study from Norway - Julie Solberg Knutsen; Gunnar Tschudi Bondevik; Steinar Hunskaar (Scandinavian Journal of Primary Health Care, 2024)
Objective Many countries experience challenges in recruiting and retaining general practitioners (GPs) as supervisors for medical students in clinical placements. We aimed to investigate the opportunities, capacities and limitations of Norwegian GPs to become supervisors.Design Web-based cross-sectional questionnaire study.Setting Norwegian general practice.Subjects All GPs in Norway, including locums and those on leave, both active supervisors, and GPs who are not presently supervising medical students.Main outcome measures GPs’ terms of salary, office facilities, limiting factors, capacity and needs for becoming or continuing as supervisors.Results Among 5145 GPs, 1466 responded (29%), of whom 498 (34%) were active supervisors. Lack of a dedicated student office was the most reported limitation for both active supervisors (75%) and other GPs (81%). A high proportion (67%) of active supervisors reported that they could host more students per year, given financial support for equipped offices and higher salaries. With this kind of support, 48% (n = 461) of the GPs who were not supervisors for medical students were positive about a future supervisor role. By adjusted regression analysis, female GPs had lower likelihood of being supervisors, OR (95% CI) 0.75 (0.59–0.95) than male colleagues. GPs in the North, Mid and West regions had higher odds (OR 3.89, 3.10 and 2.42, respectively) than those in the South-East region. Teaching experience also increased the odds (2.31 (1.74–3.05).Conclusions There seems to be capacity among both active and potential supervisors if increased salaries and financial support for office facilities are made available.